Responding to Covid-19 Pandemics and Afflictions: A Sufi Perspective - Meerasahibu, Dheen Mohamed Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
This paper is an attempt to approach the Covid 19 pandemic from the vantage point of the Sufi tradition which is the spiritual dimension of Islam. Based on the guidance of the Qur’ān and the Prophetic examples, Sufis have contributed to the Islamic spiritual and psychological domains to the extent that their science, Tasawwuf, itself was termed by them Psychology, ʻilm al-nafs. Utilizing some of the basics of their tradition and employing analytic methodology accompanied by insights from semantics, philosophy, psychology, and history, the paper endeavours to present the Sufi approach to pandemics in simple language. The aim is to draw attention to this usually ignored approach in the context of this pandemic and to highlight some of what, I believe to be useful means of solace for the modern man who is caught between the rim and axis of this affliction. It also can provide him with some necessary inspiration as to how to free himself from depression and be optimistic, especially in times of pandemics and afflictions. The paper also seeks to remind the reader of the importance of the worldview one holds in any discussion related to human life and cosmic events.